ANALISIS PENDAPATAN USAHATANI PADI SAWAH DI DESA TOUNTIMOMOR KECAMATAN KAKAS BARAT KABUPATEN MINAHASA (Analysis of Rice Rice Business Income In Tountimomor Village, West Kakas Sub District, Minahasa Regency) - Jesica Octavia Najoan; Rine Kaunang; Grace A. J. Rumagit (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
The objective of this research is to determine the cost structure of lowland rice in Tountimomor Village, Kakas Barat District, Minahasa Regency. The research results showed that the average land area of the respondent farmers was 1.42 Ha, the total revenue per hectare was Rp. 21,787.985, with a total cost of the sample farmers in theÂ  rice farming of Rp. 8.787.084, while the average farmers' production ofÂ  rice farming was 140.625 kg. The income of the sample farmers of rice in the study area is Rp. 12.960.921. The rice farming is feasible to run because the R / C value was 2,51.